Effectiveness of sleep interventions for rotating night shift workers: a systematic review and meta-analysis - Jeon, Bo Min; Kim, Su Hyun; Shin, Seung Hwa (Frontiers in Public Health, 2023)
Background: Sleep disturbance is a common issue among rotating night shift workers and is closely related to health risks. The present study aimed to determine the effectiveness of pharmacological and nonpharmacological sleep interventions for the management of sleep disturbance among rotating night shift workers. Methods: For this systematic review and meta-analysis, we searched six electronic databases— EMBASE, CINAHL, Cochrane Library, PubMed, Scopus, and Web of Science— for randomized controlled trials and clinical trials published from January 1990 to June 2022. The quality of eligible studies was independently assessed by three authors using the Joanna Briggs Institute Critical Appraisal Checklist for randomized controlled trials and quasi-experimental studies. The meta-analysis was performed based on the random effects model using the Comprehensive Meta-Analysis software. The study was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Results: Of the 1019 studies retrieved, 30 met the inclusion criteria for the systematic review; 25 were selected for the meta-analysis. Sleep interventions were categorized as follows: pharmacological approach (n = 7), light therapy (n = 9), cognitive behavioral approach (n = 7), aroma or alternative therapy (n = 4), and shift schedule modification (n = 3). The overall mean effect size of the interventions was moderate (Hedges’ g = 0.59; 95% confidence interval = 0.33–0.84, z = 4.50, p < 0.001). Conclusion: Sleep interventions were effective in promoting sleep or reducing sleep disturbance among rotating night shift workers. These findings provide evidence of the effectiveness of various pharmacological and nonpharmacological sleep interventions for managing sleep health in the work environment of rotating night shift workers.